Physiological and metabolomic responses of adzuki bean (Vigna angularis) to individual and combined chilling and waterlogging stress - Xiaoyan Liang; Wan Li; Huan Lu; Shihong Zhao; Jidao Du; Jidao Du; Hongtao Xiang (Frontiers in Plant Science)
IntroductionClimate change exacerbates combined environmental stresses, leading to significant crop losses globally.MethodsThis study investigated the physiological and metabolomic responses of adzuki bean (Vigna angularis) leaves to individual and combined chilling-waterlogging stresses during the flowering stage.Results and discussionResults demonstrated that both stresses significantly inhibited photosynthesis, elevated reactive oxygen species accumulation, and induced membrane lipid peroxidation. Waterlogging exhibited more severe impacts, triggering extreme ABA accumulation and plant death at 4 days post-treatment, resulting in total yield loss. Notably, combined stresses induced antagonistic effects, reducing photosynthetic decline by 14.10-32.40% and mitigating oxidative damage by 5.79-10.75% compared to waterlogging alone after 4 days. Metabolomic analysis revealed that combined stress activated more metabolic pathways than individual stress, including flavone/flavonol biosynthesis and cGMP-PKG signaling, which are critical for plant adaptation.ConclusionThis study provides valuable insights into the physiological and metabolic mechanisms underlying adzuki bean’s response to combined chilling-waterlogging stress.